2005
DOI: 10.1001/archinte.165.11.1298
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in Overweight Adults and the Long-term Risk of Hypertension

Abstract: A modest weight loss, particularly when sustained, substantially lowers the long-term risk of hypertension in overweight adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…In our study, underweight BMI in both men and women had a lower risk of hypertension compared to those with normal BMI, which was consistent with previous studies. The Framingham cohort study demonstrated a lower risk of hypertension in overweight and obese participants who have a long-time reduction of weight (Moore et al, 2005). In addition, a three-year randomized clinical trial showed that long-term weight loss was associated with decreased risk of hypertension starting from 6 months suggesting that weight reduction should be an effective method for primary prevention of risk hypertension (Stevens et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, underweight BMI in both men and women had a lower risk of hypertension compared to those with normal BMI, which was consistent with previous studies. The Framingham cohort study demonstrated a lower risk of hypertension in overweight and obese participants who have a long-time reduction of weight (Moore et al, 2005). In addition, a three-year randomized clinical trial showed that long-term weight loss was associated with decreased risk of hypertension starting from 6 months suggesting that weight reduction should be an effective method for primary prevention of risk hypertension (Stevens et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Data from population-based cohort studies demonstrate that overweight and obese adults who lose weight benefit from improvements in cardio-metabolic risk [5], [6] similar to the effects reported in weight loss trials [7]–[9]. Recent events in Cuba illustrate the dramatic reductions in diabetes incidence and mortality during a period of economic crisis that produced an average 5.5 kg weight loss over the whole population; which reversed just as dramatically when economic conditions improved and population weights rebounded [10].…”
Section: Introductionmentioning
confidence: 99%
“…(1-3) Conversely, weight loss among overweight and obese individuals has shown BP-lowering benefits. (4, 5) The mechanisms underlying these observations remain unclear. Recently, adipose tissue is characterized as an endocrine organ that produces a variety of biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%